DYNAMICS OF THE COMPOSITE STOCK PRICE INDEX, INTEREST RATES, AND EXCHANGE RATES AMID GLOBAL VOLATILITY (2021–2025) - Dhiwa Abiyu Alfattah; Irma Febriana MK (Journal Informatic, Education and Management (JIEM), 2026)
This study analyzes the dynamics of the relationship between the Jakarta Composite Index (JCI), the benchmark interest rate (BI-7DRR), and the rupiah exchange rate (IDR/USD) with global volatility (VIX), the US stock market (S&P 500), and world gold prices in the period January 2021– December 2025. Using the Vector Autoregression (VAR)/Vector Error Correction Model (VECM) approach with monthly data , this study applies the Johansen cointegration test , Impulse Response Function (IRF), and Forecast Error Variance Decomposition (FEVD). The results of the study found six cointegration vectors that confirmed a strong long -term equilibrium relationship between all variables . The IRF analysis shows that a positive shock to the VIX produces a persistent negative response to the JCI ( reaching -58.60 in the 10th period ), while the shock to the S&P 500 produces a positive response that continues to strengthen (101.39 in the 10th period ). An interesting finding shows that positive shocks to gold prices and the BI-7DRR actually generate a positive response to the JCI, contrary to conventional theoretical predictions . Exchange rate depreciation generates a persistent negative response to the JCI. The FEVD results reveal that the JCI's own-shock contributes 84.10% to its variation , followed by the S&P 500 (8.91%), gold prices ( 8.92%), and the JCI's own-shock (8.91%). (4.57% ) , VIX (1.65%), exchange rate (0.50%), and BI-7DRR (0.27%). Global factors collectively contributed 15.13% to the JCI's fluctuations , far exceeding domestic policy variables (0.77%), confirming that the Indonesian capital market in the post-pandemic period was largely driven by the dynamics of the global financial cycle .